2002
DOI: 10.2337/diacare.25.12.2153
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Metformin Therapy During Continuous Subcutaneous Insulin Infusion Treatment of Type 1 Diabetic Patients

Abstract: OBJECTIVE -This study was designed to assess the insulin-sparing effect of oral administration of metformin along with a continuous subcutaneous insulin infusion (CSII) for the treatment of type 1 diabetic patients.RESEARCH DESIGN AND METHODS -A total of 62 patients (25 women and 37 men) were studied in a monocenter, randomized, double-blind placebo-controlled study, comparing metformin (850 mg b.i.d.) with placebo in association with CSII during a 6-month period.RESULTS -Treatment with metformin was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
111
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(128 citation statements)
references
References 35 publications
12
111
4
Order By: Relevance
“…Of the remaining 12 publications, one concerned insulin-requiring type 2 diabetes rather than type 1 diabetes (noted after translation) [61], and one covered a treatment period of fewer than 7 days [62]. Only ten studies were therefore identified [16,17,20,21,23,25,26,[63][64][65]. One of these, which was conducted on participants living in a children's home and did not mention informed consent, was excluded from further analysis [64].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 12 publications, one concerned insulin-requiring type 2 diabetes rather than type 1 diabetes (noted after translation) [61], and one covered a treatment period of fewer than 7 days [62]. Only ten studies were therefore identified [16,17,20,21,23,25,26,[63][64][65]. One of these, which was conducted on participants living in a children's home and did not mention informed consent, was excluded from further analysis [64].…”
Section: Resultsmentioning
confidence: 99%
“…The final nine studies [16,17,20,21,23,25,26,63,65] covered a total of 192.8 patient years, and the number of completed participants ranged from ten to 92 (median 26) (two studies did not report number completed [17,26]) ( Table 1). The total maximum daily metformin dose varied from 1,000 to 2,550 mg; duration of therapy ranged from 7 days to 12 months (median 4 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such strategy is the addition of a drug that improves insulin sensitivity such as metformin, a biguanide that acts principally by increasing insulin sensitivity in the liver by inhibiting hepatic gluconeogenesis and thereby reducing hepatic glucose production [75]. Other minor mecha-nisms include decreasing fatty acid oxidation and intestinal glucose absorption [76], and increasing peripheral insulin sensitivity by enhancing glucose uptake in the muscles [77]. Metformin has mainly been used in adult patients with T2D and several studies have shown beneficial effects on body weight, blood lipid levels and metabolic control [78][79][80].…”
Section: Alternative Therapeutic Strategiesmentioning
confidence: 99%
“…Randomized controlled trials with metformin in adolescents with T2D reported an improvement in fasting plasma glucose level [81]. However, there have been conflicting reports from studies in adolescents with T1D [75][76][77]82,83]. The benefit was transient in one study [83] and negative in another [82].…”
Section: Alternative Therapeutic Strategiesmentioning
confidence: 99%